Genome Sequencing of Rahnella victoriana JZ-GX1 Provides New Insights Into Molecular and Genetic Mechanisms of Plant Growth Promotion - Kong, Wei-Liang; Wang, Wei-Yu; Zuo, Sheng-Han; Wu, Xiao-Qin (Frontiers in Microbiology, 2022)
Genomic information for bacteria within the genus Rahnella remains limited. Rahnella sp. JZ-GX1 was previously isolated from the Pinus massoniana rhizosphere in China and shows potential as a plant growth-promoting bacterium. In the present work, we combined the GridION Nanopore ONT and Illumina sequencing platforms to obtain the complete genome sequence of strain JZ-GX1, and the application effects of the strain in natural field environment was assessed. The whole genome of Rahnella sp. JZ-GX1 comprised a single circular chromosome (5,472,828 bp, G+C content of 53.53%) with 4,483 protein-coding sequences, 22 rRNAs, and 77 tRNAs. Based on whole genome phylogenetic and average nucleotide identity (ANI) analysis, the JZ-GX1 strain was reidentified as R. victoriana. Genes related to indole-3-acetic acid (IAA), phosphorus solubilization, nitrogen fixation, siderophores, acetoin, 1-aminocyclopropane-1-carboxylate (ACC) deaminase, gamma-aminobutyric acid (GABA) production, spermidine and volatile organic compounds biosynthesis were present in the genome of strain JZ-GX1. In addition, these functions were also confirmed by in vitro experiments. Importantly, compared to uninoculated control plants, Pyrus serotina, Malus spectabilis, Populus euramericana (Dode) Guinier cv. ‘San Martino’ (I-72 poplar) and Pinus elliottii plants inoculated with strain JZ-GX1 showed increased heights and ground diameters. These findings improve our understanding of R. victoriana JZ-GX1 as a potential biofertilizer in agriculture.